0 Rajan@2021Guru Asked: May 10, 20212021-05-10T13:20:41+05:30 2021-05-10T13:20:41+05:30In: CBSE Solve: 3/(x+y) + 2/(x-y) = 2 and 9/(x+y) – 4/(x-y) = 1 0 This question is taken from linear equations in two variables in which we have been asked to find the value of 3/(x+y) + 2/(x-y) = 2 and 9/(x+y) – 4/(x-y) = 1 RS Aggarwal, Class 10, chapter 3F, question no 21 cbse class 10linear equations in two variablesrs aggarwal Share Facebook 1 Answer Voted Oldest Recent MathsMentor Guru 2021-05-10T13:52:42+05:30Added an answer on May 10, 2021 at 1:52 pm Let 1/(x+y)=X and 1/(x−y)=Y 3X+2Y=2 …(i) 9X−4Y=1 …(ii) On multiplying (i) by 3 and (ii) by 1 and subtracting, we get 9X+6Y=6 −9X+−4Y=−1 10Y=5 ∴Y=1/2 On putting Y=1/2 in (i), we get 3X+2×1/2=2 ⇒X=1/3 ∴1/(x+y)=1/3 and 1/(x−y)=1/2 ⇒x+y=3 …(iii) x−y=2 …(iv) On adding (iii) and (iv), we get 2x=5 ⇒x=5/2 On putting x=25 in (iii), we get 5/2+y=3 ⇒y=3−5/2=1/2 ∴x=5/2, y=1/2 0 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment. Related Questions A boat goes 24km upstream and 28km downstream in 6 hours. It goes 30km upstream and 21km downstream ... Solve the following quadratic equation: √2x²+7x+5√2=0. Solve the following quadratic equation: x²+3√3x-30=0 Solve the following quadratic equation: x²-(√3-1)x+√3=0 Solve the following quadratic equation: x²-3√5x+10=0

## Let 1/(x+y)=X and 1/(x−y)=Y

3X+2Y=2 …(i)

9X−4Y=1 …(ii)

On multiplying (i) by 3 and (ii) by 1 and subtracting, we get

9X+6Y=6

−9X+−4Y=−1

10Y=5

∴Y=1/2

On putting Y=1/2 in (i), we get

3X+2×1/2=2

⇒X=1/3

∴1/(x+y)=1/3 and 1/(x−y)=1/2

⇒x+y=3 …(iii)

x−y=2 …(iv)

On adding (iii) and (iv), we get

2x=5

⇒x=5/2

On putting x=25 in (iii), we get

5/2+y=3

⇒y=3−5/2=1/2

∴x=5/2, y=1/2